2014
DOI: 10.1107/s1600536814005790
|View full text |Cite
|
Sign up to set email alerts
|

1-Phenylpiperazine-1,4-diium tetrachloridocobalt(II)

Abstract: In the title mol­ecular salt, (C10H16N2)[CoCl4], the piperazine ring of the phenyl­piperazine dication adopts a chair conformation and the phenyl ring occupies an equatorial orientation. In the tetra­chlorido­cobaltate(II) dianion, the Co—Cl bond lengths for the chloride ions not accepting hydrogen bonds are significantly shorter than those for the chloride ions accepting such bonds. In the crystal, the components are linked by N—H⋯Cl hydrogen bonds, generating [001] chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In the [CoCl 4 ] 2À anion, the Co-Cl bond lengths range from 2.2645 (12) to 2.2934 (12) Å and the Cl-Co-Cl angles range from 104.84 (5) to 118.58 (5) , revealing considerable distortions from the ideal tetrahedral geometry. These values are in agreement with those observed in similar compounds (Dhieb et al, 2014;Mghandef & Boughzala, 2014;Oh et al, 2011). The different Co-Cl bond lengths in the [CoCl 4 ] 2À anion are related to the number of hydrogen bonds accepted by the Cl atoms.…”
Section: Figuresupporting
confidence: 91%
“…In the [CoCl 4 ] 2À anion, the Co-Cl bond lengths range from 2.2645 (12) to 2.2934 (12) Å and the Cl-Co-Cl angles range from 104.84 (5) to 118.58 (5) , revealing considerable distortions from the ideal tetrahedral geometry. These values are in agreement with those observed in similar compounds (Dhieb et al, 2014;Mghandef & Boughzala, 2014;Oh et al, 2011). The different Co-Cl bond lengths in the [CoCl 4 ] 2À anion are related to the number of hydrogen bonds accepted by the Cl atoms.…”
Section: Figuresupporting
confidence: 91%
“…It is also used in the synthesis of dyes, agrochemicals and other pharmaceutical compounds. The crystal structures of compounds derived from 1-ethylpiperazine, viz., chlorobis- (2-chlorobenzyl)(4-ethylpiperazine-1-dithiocarbamato-2 S,S 0 )tin(IV) (Li & Li, 2007), 1-diphenylmethyl-4-ethylpiperazine-1,4-diium dichloride (Qiao et al, 2010), (S)-3chloro-4-(4-ethylpiperazin-1-yl)-5-[(1R,2S,5R)-2-isopropyl-5methylcyclohexyloxy]furan-2(5H)-one (Fu et al, 2010), 4-{[5-(4-chlorophenyl)-1-(4-fluorophenyl)-1H-pyrazol-3-yl]carbon-yl}-N-ethylpiperazine-1-carboxamide (Shahani et al, 2011), 2-[4-(2-methoxyphenyl)piperazin-1-yl]-N-(pyridin-2-yl)acetamide (Lu & Jiang, 2011), N-(4-chlorophenyl)-4-ethylpiperazine-1-carboxamide (Li, 2011) and trichlorido(1ethylpiperazin-1-ium)cobalt(II) (Dhieb et al, 2014) have been reported.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The formation of complexes between organic molecules and cobalt-isothiocyanate moieties is especially important for their use in diverse fields of technological applications [24,25]. In view of the importance of piperazines the structural chemistry of various compounds that include piperazine and its derivatives does not cease to develop and continues to be a subject of research in many laboratories [26][27][28][29][30][31][32][33][34][35][36]. Piperazine and its derivatives have plentiful potential applications and are important ligands for constructing coordination complexes.…”
Section: Introductionmentioning
confidence: 99%